Innovative Drone Technology for Property Maintenance - Mazelan, Aliff Khuzairi; Shamsudin, Zarina; Mat Radzuan, Indera Syahrul; Mohsen, Masfaliza (Research in Management of Technology and Business, 2025)
The use of drone technology in property maintenance provides new, creative and safety for the property management industry with privacy concerns and regulatory barriers as the key challenges to adapt this technology. The study identified five main contributions such as improving operational efficiency, enhancing safety, reducing costs solution for managing high-rise buildings and hard-to-reach areas. This study looks at how drones can be used in property management field, focusing on how effective they are and the challenges of using them. The research was based on interviews and reviewing articles. Through qualitative research involving interviews with industry experts, the findings reveal that drones significantly enhance inspection efficiency, improve safety and reduce costs through capabilities such as AI-powered predictive maintenance and real time data collection. Experts emphasized that drone's cost-effectiveness, addressing regulatory restrictions and advancing technological integration. However, there are challenges, such as rules related, technical issues and cost. This study helps with ideas for managing properties in a more sustainable way and gives tips for solving problems with drone implementation. Future studies should focus on technology handling and regulation to make drones even more useful and widely benefited to the industry.